Isatuximab plus carfilzomib-dexamethasone versus carfilzomib-dexamethasone in patients with relapsed multiple myeloma (IKEMA): overall survival analysis of a phase 3, randomised, controlled trial - Yong, Kwee; Martin, Thomas; Dimopoulos, Meletios-Athanasios; Mikhael, Joseph; Capra, Marcelo; Facon, Thierry; Hajek, Roman; Špička, Ivan; Baker, Ross; Kim, Kihyun; Martinez, Gracia; Min, Chang-Ki; et al. (The Lancet. Haematology, 2024)
BACKGROUND: Isatuximab is an anti-CD38 monoclonal antibody approved for the treatment of relapsed or refractory multiple myeloma. Previous analyses of the IKEMA trial showed prolonged progression-free survival in patients with this disease who received isatuximab in combination with carfilzomib-dexamethasone as compared with those who received carfilzomib-dexamethasone alone. Herein, we report the analysis of overall survival from the IKEMA trial. METHODS: This prospective, randomised, open-label, active-controlled, phase 3 study included patients with relapsed or refractory multiple myeloma aged 18 years or older, who had received one to three previous lines of treatment from 69 study centres in 16 countries across North America, South America, Europe, and the Asia-Pacific region. Patients were randomly allocated (3:2) to treatment with either isatuximab plus carfilzomib-dexamethasone (isatuximab group) or carfilzomib-dexamethasone (control group). In the isatuximab group, patients received intravenous isatuximab (10 mg/kg on days 1, 8, 15, and 22 of the first 28-day cycle, and days 1 and 15 of subsequent 28-day cycles). In both treatment groups, intravenous carfilzomib (20 mg/m2 on days 1 and 2 of the first cycle; and 56 mg/m2 on days 8, 9, 15, and 16 of the first cycle, and days 1, 2, 8, 9, 15, and 16 of subsequent cycles) and intravenous or oral dexamethasone (20 mg on days 1, 2, 8, 9, 15, 16, 22, and 23) were administered. The primary endpoint of the trial was progression-free survival, which was reported previously. Treatment continued until progression, unacceptable toxicity, or patient request to discontine. The overall survival analysis reported here was planned to be conducted 3 years after the primary progression-free survival analysis in the intention-to-treat population. Additional analyses were conducted on the secondary endpoints of time to next treatment and second-progression-free survival. Reported p values are non-inferential due to hierarchical testing. This trial is registered with ClinicalTrials.gov (NCT03275285). FINDINGS: Between Nov 15, 2017, and March 21, 2019, 302 patients were enrolled and randomly allocated: 179 (59%) to the isatuximab group and 123 (41%) to the control group. 169 (56%) patients were male, 133 (44%) were female, 214 (71%) were White, 50 (17%) were Asian, nine (3%) were Black or African American, and three (1%) were multiracial. At data cutoff for this overall survival analysis (Feb 7, 2023), 79 (44%) overall survival events in the isatuximab group and 59 (48%) in the control group had occurred (median follow-up 56·61 months [IQR 54·90-58·02]). Median overall survival (in months) was not reached (NR; 95% CI 52·17-NR) in the isatuximab group and was 50·60 months (38·93-NR) in the control group (hazard ratio [HR] 0·855 [95% CI 0·608-1·202], nominal one-sided p=0·18). Survival probability at 48 months was 59·7% (95% CI 52·0-66·7) in the isatuximab group and 52·2% (95% CI 42·7-60·8) in the control group (based on Kaplan-Meier analysis). Improvements in time to next treatment (HR 0·583 [95% CI 0·429-0·792], nominal one-sided p=0·0002) and second-progression-free survival (0·663 [0·491-0·895], nominal one-sided p=0·0035) were observed in the isatuximab group. The most common treatment-emergent adverse events were infusion reactions (82 [46%] patients in the isatuximab group and four [3%] in the control group) and upper respiratory tract infections (71 [40%] and 34 [28%], respectively). Discontinuations due to treatment-emergent adverse events were similar between treatment groups (24 [14%] in the isatuximab group and 22 [18%] in the control group), despite an additional 30 weeks of exposure in the isatuximab group. 12 (7%) patients in the isatuximab group and six (5%) patients in the control group had a treatment-related adverse event with a fatal outcome during study treatment. INTERPRETATION: At the time of the current analysis, a difference in overall survival could not be detected between the treatment groups, and no new safety signals were observed. Collectively, the evidence suggests that isatuximab plus carfilzomib-dexamethasone is a key treatment for patients with relapsed or refractory multiple myeloma. FUNDING: Sanofi.
Keywords: dexamethason; Humans; lidé středního věku; analýza přežití; Oligopeptides; Multiple Myeloma; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; senioři; lidé; humanizované monoklonální protilátky; oligopeptidy; doba přežití bez progrese choroby; Survival Analysis; mnohočetný myelom; Adult; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Progression-Free Survival; lokální recidiva nádoru; mužské pohlaví; prospektivní studie; Neoplasm Recurrence, Local; Prospective Studies